Library of Souls - Riggs, Ransom (Philadelphia, PA : Quirk Books, 2015)
When a madman is on the loose and Miss Peregrine in peril, Peculiar Children Jacob Portman and Emma Bloom stage rescue missions, meet new allies, and face great dangers.
Keywords: Orphans -- Juvenile fiction; Teenagers -- Juvenile fiction; Rescues -- Juvenile fiction; Paranormal fiction; Orphans -- Fiction; Teenagers -- Fiction; Rescues -- Fiction; Supernatural -- Fiction; London (England) -- Juvenile fiction; London (England) -- Fiction; Paranormal fiction